Simulation in training nurses: reflections and justifications based on bioethics and human rights approaches - Raniere de Oliveira Costa, Raphael; de Medeiros, Soraya Maria; Amado Martins, José Carlos; Dias Coutinho, Verónica Rita (Acta Bioethica, 2018)
The aim of this paper is to reflect about the use of simulation in training nurses based on bioethics and human rights approaches. This is a reflexive essay based on the assumption that the current training context in health and nursing must include in the process teaching and learning strategies which take into account diverse ethical and bioethical questions about human rights, technological development and scientific knowledge. The use of simulation in training nurses is justified on human dignity, not in the instrumentalization of the person, equity and not discrimination. Furthermore, some fundamental principles of bioethics and their relation to simulation are pointed out. Moreover, the contributions of this teaching and learning strategy are discussed under the perspectives of patient/user, student, university and health care institution. Considering these issues, it is essential to plan a training practice incorporating these dimensions in the training process of future nurses.